A copper(ii) metal–organic hydrogel as a multifunctional precatalyst for CuAAC reactions and chemical fixation of CO2 under solvent free conditions. Issue 9 (17th January 2017) - Karan, Chandan Kumar; Sau, Mohan Chandra; Bhattacharjee, Manish
Abstract : A copper(ii ) metal–organic gel has been synthesized. This metal–organic gel is an efficient reusable catalyst for CuAAC and conversion of CO2 to cyclic carbonates. Abstract : A copper(ii ) metal–organic hydrogel has been synthesised and characterised. This hydrogel is an efficient, reusable precatalyst for CuAAC reactions and chemical fixation of CO2 under solvent free conditions.